2002
DOI: 10.1163/156854002760202688
|View full text |Cite
|
Sign up to set email alerts
|

Colour Change and Mimicry From Juvenile to Adult: Xantho Poressa (Olivi, 1792) (Brachyura, Xanthidae) and Carcinus Maenas (Linnaeus, 1758) (Brachyura, Portunidae)

Abstract: For two years we have studied carapace colour change, mimicry, and substrate choice during the juvenile stages of two species of crabs, Xantho poressa and Carcinus maenas. Both species live in the Posidonia oceanica meadows until their last moult, after which they abandon the prairies for the nearest rocky substrate (Xantho) or for soft sea bottoms (Carcinus). RIASSUNTO Per due anni sono stati studiati la variabilità del cambiamento di colore del carapace, mimetismo e scelta del substrato negli stadi giovanili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 2 publications
0
20
1
Order By: Relevance
“…Bedini (2002) suggested that the juveniles have colour patterns that conform to cryptic mimicry in sea grass and that the adults change their colour at their Wnal moult to complete adulthood and move to rocky shores. However, Reuschel and Schubart (2007) argued that both juveniles and adults were found with highly variable colours, suggesting that they use diVerent colours and disruptive cryptic colouration as passive defence (camouXage).…”
Section: Discussionmentioning
confidence: 99%
“…Bedini (2002) suggested that the juveniles have colour patterns that conform to cryptic mimicry in sea grass and that the adults change their colour at their Wnal moult to complete adulthood and move to rocky shores. However, Reuschel and Schubart (2007) argued that both juveniles and adults were found with highly variable colours, suggesting that they use diVerent colours and disruptive cryptic colouration as passive defence (camouXage).…”
Section: Discussionmentioning
confidence: 99%
“…In seagrass P. oceanica meadows, Bedini (2002) collected 23 crabs ( Carcinus maenas and X. poressa ) during 2 years by SCUBA diving at a depth of 20–30 m and suggested that this represents the juvenile habitat of X. poressa . According to our results and the small sample size of Bedini, the collected specimens of Bedini (2002) must represent a very small fraction of the overall size class and have settled in the sea grass meadows in absence of more suitable habitat. Concerning the adult specimens, also Riedl (1983) described X. poressa as a common species in shallow harbours and shores, mostly occurring under stones.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatic changes during the ontogeny of crustaceans have been reported by Abele (1982) and Dalabona et al (2005), particularly changes associated with maturation, as observed for other decapods of the genera Callinectes (Baldwin and Johnsen, 2012) and Arenaeus (Pinheiro and Taddei, 2000). In this study, there was a relationship between the size (TL) of females with red carapaces (range: 16.5-29.0 cm TL; mean; 22.7 cm TL [SD 2.9]) and L 50 (25.3 cm TL), a size that was very similar to the smallest ovigerous female registered in this study (22.5 cm TL).…”
Section: Discussionmentioning
confidence: 53%